Racial and socioeconomic disparities among patients undergoing hip arthroplasty: a New York State population analysis. Issue 4 (July 2021) - Darbandi, Aria
Abstract : Background: Hip arthroplasty places a large economic burden on the United States healthcare system, and there is a need to better understand influencing factors to help prepare for and limit expenditures. We aimed to assess racial and socioeconomic factors that influence hospital charges and length of stay using the New York State population. Methods: This study used the publicly available New York Statewide Planning and Research Cooperative System (SPARCS) database to identify hip replacement cases from 2013 to 2016 in New York State. Multivariable logistic regression models were used to examine characteristic differences between white and black patients. Multivariable linear models were used to identify predictive variables for hospital charges and length of stay. Results: White patients had lower mean length of stay (3.61 vs. 4.35, P <0.0001) and hospital charges ($55, 988 vs. $67, 742, P <0.0001). Medicaid patients were more likely to be black compared to the privately insured (OR: 4.37, CI: 4.08 to 4.68). Black race predicted higher hospital charges and length of stay ( P <0.0001). Medicaid predicted longer length of stay ( P <0.0001). Conclusions: Racial and insurance-based disparities exist among hip replacement patients, and these factors influence length of stay and hospital charges. These tendencies should be noted by healthcare administrators to limit the economic burden of hip arthroplasty. Level of Evidence: Level III